2017
DOI: 10.1007/s00167-017-4769-2
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable loop ACL suspension devices demonstrate less reliability in terms of reproducibility and irreversible displacement

Abstract: Adjustable loop devices still show biomechanical inferiority and demonstrate heterogeneity of fixation properties with wide- and less-reproducible displacement ranges resultant to the mechanism of adjustment, denoting less reliability. However, three adjustable devices (RIGIDLOOP™ Adjustable, Ultrabutton , ProCinch™) demonstrate fixation capacities within the margins of clinical acceptance. RIGIDLOOP™ Adjustable provides the most comparable fixation properties to fixed loop devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 11 publications
5
38
0
Order By: Relevance
“…Adjustable CFDs based on the sling lock mechanism, however, have exhibited unsatisfactory mechanical performance even when subjected to moderately high-cyclic forces. 1 The present study describes an adjustable-length fixation device based on a modified sling lock mechanism. The device comprises 1 loading suture with a stopper knot and a titanium suspension button with 6 holes.…”
mentioning
confidence: 99%
“…Adjustable CFDs based on the sling lock mechanism, however, have exhibited unsatisfactory mechanical performance even when subjected to moderately high-cyclic forces. 1 The present study describes an adjustable-length fixation device based on a modified sling lock mechanism. The device comprises 1 loading suture with a stopper knot and a titanium suspension button with 6 holes.…”
mentioning
confidence: 99%
“…Some mechanical studies that compared adjustable-loop devices and fixed-loop devices reported that the latter showed higher breaking strength and less displacement Takahashi and Takahashi Journal of Experimental Orthopaedics (2020) 7:17 [18][19][20][21][22][23][24][25]. On the other hand, other studies reported no difference in either parameter [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum load level of 300 N was chosen according to previously performed studies [9,10]. Barrow et al [9] and Ahmad et al [11] defined an absolute displacement of 3 mm as clinical failure, this value was considered as failure criterion for the tested samples. For the single device test (see figure 3A) the ALDs and FLDs were fixed in the setup between two metallic components to apply loads on the device.…”
Section: Stability Test Seriesmentioning
confidence: 99%